Investigation of Metastasis-Related Genes: A Rat Model Mimicking Liver Metastasis of Colorectal Carcinoma - Adwan, Hassan; Georges, Rania; Pervaiz, Asim; Berger, Martin R. (Frontiers in Oncology, 2017)
Liver is the main target of colorectal cancer (CRC) metastasis. Currently, the number of reports is small, which describe changes in gene expression supporting liver metastasis. Here, a rat model was used for analyzing mRNA modulations during liver colonization and compared with available literature. In the model, CC531 rat CRC cells were injected via a mesenteric vein into isogenic WAG/Rij rats and re-isolated at early, intermediate, advanced and terminal stages of liver colonization. These cells were used for RNA isolation. Microarrays were used for analyzing mRNA profiles of expression. The number of deregulated genes is comparatively large and only part of it has been studied so far. As reported to date, claudins and insulin-like growth factor binding proteins were found to be deregulated. The fact that the chosen method is efficient is confirmed by the study of claudins and insulin like growth factor binding proteins, which show altered expression in the initial stages of liver colonization and then return to normalcy. In addition, cadherin was described to be down-regulated in EMT models. It can therefore be concluded that the models used are helpful in finding genes, which are instrumental for metastatic liver colonization.